Antimalarial activity of ethyl acetate extract of Garcinia dulcis kurz stem bark - Gunawan Pamudji Widodo; Mamik Ponco Rahayu (Universitas Gadjah Mada, 2010)
In-vivo antimalarial activity of ethyl acetate extract of Garcinia dulcis Kurz stem bark have been evaluated against Plasmodium berghei induced mice. Antimalarial test was conducted by paracitemia investigation and leucocyte counting of paracite induced mice blood, after oral administration of Garcinia dulcis stem bark extract dose of 25 mg, 50 mg, as well as 75 mg/kg bw. The highest antiplasmodial activity and decresing of leucocyte amount was showed by extract of dose of 50 mg/kg bw. The compounds identified in ethyl acetate extract of Garcinia dulcis stem bark were flavonoid, saponin and tannin. The compounds that have antimalarial activity weren't yet known.